Hubungan Pelayanan Imunisasi Dasar Dengan Kepuasan Ibu Bayi Di Puskesmas Perawatan Deleng Pokhisen Kabupaten Aceh Tenggara Tahun 2021 - Yani, Hazrah; Sinaga, Martaulina; Sari, Sonia Novita; Lestari, Dira; Nisak, Janatun (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
Immunization is one of the government programs that aims to improve public health. The infant mortality rate in Indonesia is still very high. It is estimated that 1.7 million children or 5% of under-five deaths in Indonesia are caused by diseases that can be prevented by immunization/PD3I. The quality of immunization services that are less than optimal will of course waste the resources that have been spent, such as operational costs, vaccines, logistics, manpower, and time. Even the most concerning for all of us is that the failure of immunization will threaten the occurrence of illness, disability, or death in children. This study aims to determine the Correlation between basic immunization services and maternal infant satisfaction at the Deleng Pokhisen Health Center, Southeast Aceh Regency in 2021. This type of research is descriptive descriptive, which is a research that explores how and why health phenomena occur with a cross sectional approach. The population is mothers who have babies aged 0-12 months. The sampling technique in this study was simple random sampling with a total of 64 people. The data analysis technique used chi square statistical test. The results obtained in this study are that there is a relationship between basic immunization services (tangibles, reliability, responsiveness, assurance, four) with the satisfaction of the baby’s mother. There is a Correlation between Basic Immunization Services and Mother Baby Satisfaction at the Deleng Pokhisen Health Center, Southeast Aceh Regency in 2021. Suggestions to the Deleng Pokhisen Care in Southeast Aceh Regency are to maintain and maintain the quality of basic immunization services so that they continue to bring their babies back for immunization